2017
DOI: 10.1155/2017/1950692
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Aqueous Extract from Horseradish Root (Armoracia rusticana Radix) against Lipopolysaccharide‐Induced Cellular Inflammation Reaction

Abstract: Horseradish (Armoracia rusticana) is a perennial crop and its root is used in condiments. Traditionally, horseradish root is used to treat bacterial infections of the respiratory tract and urinary bladder. The antiphlogistic activity, determined in activated primary human peripheral blood mononuclear cells (PBMC), was evaluated for an aqueous extract and its subfractions, separated by HPLC. Compound analysis was done by UHPLC-QToF/MS and GC-MS. The aqueous extract concentration-dependently inhibited the anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
4
11
0
7
Order By: Relevance
“…All together, our data indicated that ESE was able to reduce inflammation, mediating in this way neuroprotective effects, protecting NSC-34 motor neurons from cell death. Notably, our results showing the anti-inflammatory properties of ESE are in line with other evidence showing the anti-inflammatory properties of other Brassicaceae extracts ( 38 , 46 , 47 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All together, our data indicated that ESE was able to reduce inflammation, mediating in this way neuroprotective effects, protecting NSC-34 motor neurons from cell death. Notably, our results showing the anti-inflammatory properties of ESE are in line with other evidence showing the anti-inflammatory properties of other Brassicaceae extracts ( 38 , 46 , 47 ).…”
Section: Discussionsupporting
confidence: 92%
“…ESE was shown to decrease COX2 gene expression level in a model of rat mammary gland carcinogenesis induced by 7,12 dimethylbenz(α)anthracene (DMBA), and to exert antioxidant, anti-inflammatory and anticancer activities ( 37 ). Moreover, other Brassicaceae extracts were able to inhibit COX2 expression ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The essential oils and the volatile fraction of other extracts obtained from Brassicaceae species often contain nitriles and/ or isothiocyanates derived from glucosinolate breakdown, although their contents can strongly vary according to climatic conditions, soil and changes in the extraction procedures. For example, azeleonitrile was in the volatile fraction of an aqueous root extract from Armoracia rusticana [26] 4-isothiocyanate belonged to the volatile fraction of an aqueous sprout extract from Brassica oleracea and the essential oil from flowering aerial parts of Morettia phillaeana. [27,28] However, the absence of glucosinolate derivatives in the Tunisian L. maritima suggests that they were lost during drying of the plant material or there are L. maritima genotypes that are poor glucosinolate producers.…”
Section: Chemical Composition Of the Essential Oilmentioning
confidence: 99%
“…Therefore, non-toxic solvents, such as water or ethanol, are required in order to avoid toxicity issues. Herz et al prepared aqueous horseradish extracts that revealed high concentrations of volatile and non-volatile glucosinolates, amino acids and phenolic compounds; glucosinolates are later hydrolyzed to allyl-and phenylethylisothiocyanates [9]. The authors reported a strong antiinflammatory activity caused by a dual inhibition of the aminoacid metabolism with less severe side effects compared to selective COX blockers; in addition, the effects were not mediated by isothiocyanates.…”
Section: 8128mentioning
confidence: 99%
“…John Woodall assigned for the first time in 1639 the use of horseradish for scurvy [7] and about in the same period William Coles sustained that horseradish can be successfully used in treating malaria and scurvy [8]. AR remedies were also found to be helpful in many health problems: rheumatism, gout, scurvy, deficient digestion, urinary distress, headache, toothache, sciatica [6,9].…”
Section: Introductionmentioning
confidence: 99%